Impact study of the fuel type used on the energy efficiency costs values and harmful emissions generation for small, medium and large container vessels - Nikiforov Viktor (EDP Sciences, 2021)
Annually a large amount of goods has been transported over the world and the most of the transportation is carried by seaborne. Although the seaborne trade is considered to be the most efficient – economically and environmentally friendly way of transportation an enormous amount of fossil fuels is used to fulfil the operation of the merchant fleet. Although we are living in times where efforts are directed to improvement of the state of the environment and reduction of the negative impact of the Greenhouse Gases, the fossil fuels still remain the main energy source used to run the internal combustion engines widely used in the ships nowadays. A well-known fact is that the fuel burning leads to significant harmful emissions generation causing a serious negative effect on the surrounding us environment. The introduced by IMO and MEPC requirements regarding the Greenhouse Gases (GHG) imposes for development and application of new criteria when selecting the ship’s propulsion plant. In the current article will be observed three ship groups consisting of real container vessels. The purpose is to analyse the impact caused by the fuel type used in the ship’s engines on the GHG generation and the economic indicators related with fuel costs